The balance of pressor and depressor substances in the neurons of arcuate nucleus of hypothalamus in etiologically different arterial hypertension - Tishchenko, S. V. (Journal of Education, Health and Sport, 2019)
It has been proved that arterial hypertension is not associated exclusively with an increase in vascular tone but also with a complex of pathological processes that results in cardiovascular pathology and lesions of the target organs. The central and peripheral contours of blood pressure regulation are well studied. Nevertheless, despite the presence of two regulatory contours the key structure that integrates and controls their function is the hypothalamus, in particular its arcuate nucleus. It is proved that the effectiveness of blood pressure regulation depends on those neuromodulators and neurohormones that are synthesized in the hypothalamus or transported to it. The most important neurohormones in the regulation of arterial blood presssure are brain natriuretic peptide, β-endorphin, neurotensin and angiotensin II. Equally important factor is the functional state of arcuate nucleus neurons, which depends on adequate blood supply, innervation and inter-neuronal relationships. The link between the above described processes is nitrogen monoxide system (NOS) and its universal messenger – nitric oxide NO. The purpose of the work was to determine the nature of the balance of pressor (angiotensin II and neurotensin) and depressor (brain natriuretic peptide and β-endorphin) neurohormones in the neurons of the arcuate nucleus of the hypothalamus and the ratio of NOS isoforms with hypertension of different etiology. Materials and methods. The studies were conducted on 32 mature male Wistar rats and 16 male spontaneously hypertensive rats. To study the content of neuropeptides and NOS enzyme isoforms, an immunohistochemical method was used, followed by digital image processing by Image J. The results that were obtained were calculated using the "Statistica 11.0" program. Conclusions 1. The same changes of neuropeptides’ content in hypothalamic arcuate nucleus are observed in the rats with arterial hypertension which are characterized by a decrease in the brain natriuretic peptide, β-endorphin and angiotensin II content with a significant increase in neurotensin content regardless of arterial hypertension etiology and pathogenesis. The peculiarities of the balance between depressor and pressor substances depend on the etiopathogenetic mechanisms – with the endocrine-salt model of arterial hypertension there is a significant predominance of depressor neuropeptides (in 4.3 times) whereas in essential hypertension this balance is similar to the control. 2. The changes of the NOS isoform ratio in the arcuate nucleus of hypothalamus are unidirectional, both with endocrine-salt model of arterial hypertension and essential hypertension – the content of eNOS decreases while nNOS and iNOS content increases.